Application of fuzzy linear programming method in production optimization of Batik Tulis Lasem Sumber Rejeki - Rif'atul Alawiyah; Isnarto Isnarto (Unnes Journal of Mathematics, 2023)
Production optimization is a way to regulate the use of company-owned resources. This study aims to determine: 1) Application of the Fuzzy Linear Programming method in determining the optimization of the production of Batik Tulis Lasem Sumber Rejeki. 2) Comparison of the results of the Fuzzy Linear Programming method and the original production in determining the optimization of the production of the company. 3) The response of the owner of Batik Tulis Lasem Sumber Rejeki related to research results. Data collection was carried out by observation and interviews with the owner. Furthermore, from the data, the constraint function and objective function are determined. The results of the settlement using Fuzzy Linear Programming (λ=0.51) get a maximum profit of IDR 10,400,000 if the number of one-color prime cotton hand-written batik produced is 83 sheets, one-color prime cotton hand-written batik is 15 sheets, two-color prime cotton hand-written batik 138 sheets, 12 sheets of two-color primis cotton written batik, 17 sheets of three-color prime cotton batik, and 4 sheets of three-color primis cotton written batik. Calculations made by the owner obtained a maximum profit of IDR 9,430,000 while using the Fuzzy Linear Programming method the maximum profit obtained was IDR 10,400,000..